Where is the EU’s Migrant Integration Policy Heading? - Pierre Georges Van Wolleghem (International Review of Public Policy)
This article investigates the trajectory the EU’s policy on the integration of migrants has followed in approximately 20 years of its existence. Drawing upon neofunctionalist theory, it aims to assess whether the EU’s role in the matter is expanding or stalling. Empirically, this article considers the succession of financial schemes explicitly tackling integration, in light of the fact that they constitute valuable indicators of the direction, breadth and stringency of a given policy. I therefore compare the funds allocated to integration in the 2007-2013, 2014-2020 and 2021-2027 multiannual financial frameworks. I find that the process underway is dual: whilst the EU’s role is clearly receding in terms of substantive policy points, it appears to be widening on the procedural side.